PostgreSQL 9 high availability cookbook : over 100 recipes to design and implement a highly available server with the advanced features of PostgreSQL /: over 100 recipes to design and implement a highly available server with the advanced features of PostgreSQL. (2014) - Thomas, Shaun M
No abstract available